Al-Musnad alphabet as one of the ancient Arabic vocabulary and its role in enriching graphic art - Al Srouri, Hanan; Al Thahri, Banan (Arab Journal for Sciences and Research Publishing, 2017)
The research aims to take advantage of the Musnad alphabet historical, aesthetic and artistic value that can be used in graphic design and Fine art , which have not previously appeared before in the field of graphic arts until these days The importance of research be based on it connection of Arab identity as being the first alphabets that emerged in the Arabian Peninsula , as demonstrated by numerous of studies and research that have emerged in recent decades which had a great impact on attention to Musnad alphabetic , and the possibility of using Musnad alphabets as an element of design which serves as a heritage constitutes a formed role in the history of the Arabic alphabet , and revive this heritage gives the artist a composition vocabulary emphasizes the depth of history. The artist aspires always to find a aesthetic vocabulary of design to creations a new configuration and in the same time linking him in Arab identity , and Musnad with his a geometric form letters had the aesthetics of engineering systems, gives the meditated to it feel the aesthetics of forming closer to the Pictographic stage as in hieroglyphics and reached the Ideographic stage which enables Graphic artist used it in design as an element which combines rules and assets alphabet and the aesthetics of forming.The research found the possibility of using Musnad alphabetic as design linked to Arabic identity and ancient history , the research recommends Caring of the old Arabic alphabet Heritage through the Musnad alphabet which considered a new source of forming elements to the artist